Fractional Super *- Algebra - Ucan, Yasemen (AMER INST PHYSICS, 2018)
In this study, fractional super *-algebra is defined and the fractional super *-algebra sl(2, C) is calculated for n = 3, M = 2.
Keywords: *-Hopf algebra; super *-algebra; fractional super *-algebra; SUPERSYMMETRY; ROOTS; Physics